Occupational therapy in community and population health practice - Scaffa, Marjorie E.; Reitz, S. Maggie (F.A. Davis, 2020)
This book combines the areas of occupational therapists and health educators. It is clearly and straightforwardly an occupational therapy text with an appreciation of the importance of populations and community as a context for health. The third edition aims to be a useful with a more developed discussion of the issues related to present-day community and population health practice in occupational therapy"--